A comprehensive analysis of electron emission from a-Si:H/Al2O3 at low energies. (9th February 2023) - Löffler, Janina; Belhaj, Mohamed; Bundaleski, Nenad; Diaz Leon, Juan J; Thomet, Jonathan; Frey, Samira; Ballif, Christophe; Wyrsch, Nicolas
Abstract: Recently developed microchannel plates (MCPs) based on amorphous silicon offer potential advantages with respect to glass based ones. In this context, secondary electron emission (SEE) at very low energies below 100 eV has been studied for relevant materials for these novel devices. The aim of this work was to quantify the low energy electron emission—secondary emission and elastic scattering—from amorphous silicon and alumina and the dependence of the emission energy distribution on the primary electron energy, which was previously unknown. Secondary emission and energy distribution were both modelled and measured using equipment particularly designed for this energy range. The effects of roughness, angle of incidence and surface composition were analysed. We show crossover energies as well as the angular dependence of electron emission from amorphous silicon and alumina, with a maximum experimental emission yield value of 2 and 2.8, respectively, at an incident angle of 75 ∘ . A parameterization for the energy dependence of the emission energy spectrum at low energies was derived. This extensive analysis is fundamental for a comprehensive understanding of the performance of amorphous silicon-based MCP detectors. It provides a complete model for SEE for a detailed description of the detector operation. The present results thus set the basis for a simulation framework, which is an essential element to increase the performance of these detectors and enable further developments.